2019
DOI: 10.3390/jcm8122222
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Occurrence of Hypertrophic Olivary Degeneration after Therapy of Posterior Fossa Tumors: A Single Institution Retrospective Analysis

Abstract: (1) Background: A lesion within the dentato-rubro-olivary pathway (DROP) in the posterior fossa can cause secondary neurodegeneration of the inferior olivary nucleus: so-called hypertrophic olivary degeneration (HOD). The clinical syndrome of HOD occurs slowly over months and may be overlooked in progressive neuro-oncological diseases. Posterior fossa tumors are often located near these strategic structures. The goal of this study was to analyze the systematics of HOD occurrence in neuro-oncological patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…In contrast, the midline (telovelar and transvermian), lateral or supra-cerebellar approaches mostly spared the DN, thus seldomly causing HOD. Priorly, case series had indicated that interventional treatment with damage to the GMT is predominantly responsible for HOD occurrence in neuro-oncological patients, and not tumor growth [ 5 , 6 ]. This study supports this concept, as one in five patients developed HOD post-op, but none of these tumor patients showed signs of HOD on MRI prior to neurosurgery.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, the midline (telovelar and transvermian), lateral or supra-cerebellar approaches mostly spared the DN, thus seldomly causing HOD. Priorly, case series had indicated that interventional treatment with damage to the GMT is predominantly responsible for HOD occurrence in neuro-oncological patients, and not tumor growth [ 5 , 6 ]. This study supports this concept, as one in five patients developed HOD post-op, but none of these tumor patients showed signs of HOD on MRI prior to neurosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…In posterior fossa tumor surgery, a lesion in the cerebellar dentate nucleus (DN) can trigger a series of trans-synaptic neurodegenerative events that ultimately lead to a hypertrophic olivary degeneration (HOD) of the inferior olivary nucleus in the medulla [ 1 , 2 , 3 , 4 ]. Previous clinical case series have indicated that surgical injury to the DN may be more closely associated with HOD occurrence than an invasive tumor growth [ 5 , 6 ]. However, which specific operative approaches constituted a risk factor remained unclear.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations